Correction: Tri- and hexa-nuclear NiII–MnII complexes of a N2O2 donor unsymmetrical ligand: synthesis, structures, magnetic properties and catalytic oxidase activities. Issue 10 (27th February 2020) - Mahapatra, Prithwish; Drew, Michael G. B.; Ghosh, Ashutosh
Abstract : Correction for 'Tri- and hexa-nuclear Ni II –Mn II complexes of a N2 O2 donor unsymmetrical ligand: synthesis, structures, magnetic properties and catalytic oxidase activities' by A. Ghosh et al., Dalton Trans., 2018, 47, 13957–13971.